Impact of Sustainable Marketing Activities on Customer Retention - Gurung, Bablu (KMC Journal, 2023)
Today customer retention is considered one of the most eminent drivers for the overall escalation of business enterprises. Besides, the fundamental shift in customer psychology also makes conducting sustainable marketing activities for the business more challenging. In order to address critical knowledge gaps, the present study aims to examine the impact of sustainable marketing activities on customer retention. Sustainable marketing activities include economic, social-cultural, environmental, and legal aspects. The study employed a deductive approach, causal-comparative research methods, and convenience sampling techniques for its operation. The total number of customers related to food and beverage products in the Surkhet district was taken as the target population. The study included 425 customers as a sample size. The structured questionnaire was used to collect and analyze data through descriptive and inferential statistics. The study found a significant positive impact of economic, socio_cultural, environmental, and legal sustainable marketing activities on customer retention. Therefore, business organizations should consider more sustainable marketing initiatives. The study results will serve as a source of information for stakeholders like business people, customers, researchers, and academicians.